Branding strategies for service firms- a study on the selected Internet Service Providers (ISPs) in Bangladesh - Chowdhury, Abdul Hamid; Chowdhury, Md Shahnur Azad; Imran, Mohammad (Asian Business Review, 2013)
Research work has been done on how to create a brand supporting behaviour but most of the time the existing insights have generally stemmed from research with management, brand practitioner’s and even consumers’ perspectives. Very little has been done to research the employees’ perception towards internal branding and to compare the view of the management and employees’ on internal communication. The existing researches are also done on mostly in the context of the businesses in industrialize countries whereas this research would be an intent to find the internal branding practice in a service firm in a country of developing economy. This would able to identify the gap in the practice of internal branding in different socio-economical context. This research is dedicated to find out both back end and front end skilled employees’ view towards internal communication in a service firm and based on the findings attempt would be done to see whether the staffs perceive their role differently towards the brand. For conducting the research qualitative data were gathered from the qualitative survey by questioning different employee and management about the internal brand communication and the analysis was done on that. With the respondents view on the internal marketing process, the management do not have fully structured plan to implement a sound internal branding strategy. With a given economical constraint it is not always possible to practice all the aspect of management science, but from the study of the company we can see that service firms such as ISP (internet service provider) companies in weaker economical countries could increase the internal communication practice by just altering the existing inter-departmental communication monitored by innovative senior management, co-ordination of HRM and Marketing with input from engineers.
Keywords: Branding; Strategy; Internal Marketing; ISP